Unexpected Echinococcus multilocularis infections in shepherd dogs and wolves in south-western Italian Alps: A new endemic area?. Issue 3 (December 2018) - Massolo, Alessandro; Valli, Davide; Wassermann, Marion; Cavallero, Serena; D'Amelio, Stefano; Meriggi, Alberto; Torretta, Elisa; Serafini, Matteo; Casulli, Adriano; Zambon, Laura; Boni, Chiara Benedetta; Ori, Marika; et al.
Abstract: The European distribution of Echinococcus multilocularis has been reported to be expanding east and north, whereas its southern limits are deemed stable. During a study on Echinococcus granulosus s.l. infections in wolves and dogs in the Italian Maritime Alps, we unexpectedly detected the presence of E. multilocularis eggs in four fecal samples from at least two shepherd dogs, and in five wolf fecal samples. This finding, in an area about 130 km south of the southernmost E. multilocularis report in the Alps, may suggest a rapid expansion southward. While infections in foxes are currently being investigated, these data seem to indicate the potential for a new E. multilocularis endemic area. If this will be confirmed, the implementation of surveillance programs in wild and domestic canids and preventative measures will become a priority. Graphical abstract: Image 1 Highlights: We detected Em infections in wolves and shepherd dogs 130 km south of the southern-most case reported so far in the European Union. Em infections in wolves and dogs in this area may indicate a range expansion and the establishment of a new endemic area. This area is along an ecological corridor connecting the Alps to the Apennines, with the potential for further expansion. It is priority to implement surveillance on the local fox population, and inform practitioners of the increased risk.